An organizational patterns for in-service education of teachers in Afghanistan - Muslim, Islamuddin 1935- ([Quezon City s.n.], 1972)
This study attempted to identify existing organizational patterns and working procedures at different levels of in-service education programs for teachers in Afghanistan and in some other countries. On the basis of relevant information gathered, suggestions for the improvement of in-service education for teachers in Afghanistan were formulated.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers -- In-service training -- Afghanistan